Use of Mirtazapine and Olanzapine in the Treatment of Refractory Hyperemesis Gravidarum: A Case Report and Systematic Review - Marco Aurélio Knippel Galletta; Vera Lucia Carvalho Tess; Isabela Marangon Pasotti; Luiza Fior Pelegrini; Nicole Kemberly Ribeiro Rocha; Carolina Burgarelli Testa; Rossana Pulcineli Vieira Francisco (Hindawi Limited, 2022)
Hyperemesis gravidarum (HG) is a rare condition (1.1%) characterized by excessive vomiting, malnutrition, dehydration, and laboratorial alterations. Herein, we describe the even rarer and serious presentation of refractoriness to the usual treatment of antiemetics and parenteral nutrition, with improvement only after the use of olanzapine and mirtazapine. Two subsequent pregnancies of the same woman with HG are described, which were associated with severe weight loss, anemia, hyponatremia, hypokalemia, and mild dysfunction of liver enzymes. In the third pregnancy, the usual treatment for HG was not successful, requiring enteral nutrition and the introduction of olanzapine. In the fourth pregnancy, the patient refused to use enteral nutrition for refractory HG. Hence, the patient was started on mirtazapine at an initial dose of 15 mg/day, which was gradually increased to 30 mg/day. The patient responded well to the new regimen, as demonstrated by the decrease in symptoms, the gain of 10 kg in the pregnancy, and delivering a healthy newborn. A systematic review of literature showed 11 articles and 30 cases that successfully used mirtazapine in HG. Good clinical outcomes were seen with 4 days of the treatment and at an initial dose of 15 mg/day. However, most of these reports were from psychiatric profiles, with a predominance of depression and anxiety symptoms, and a poor description of the obstetric conditions and the disease progression itself. Pulmonary hypertension was described in one case and neonatal hyperexcitability in another. The case described in this paper reinforces the idea that mirtazapine and olanzapine can be considered in refractory HG, with good results. In the world literature, this is the second case of HG that has been successfully treated with olanzapine and the first in Latin America treated with mirtazapine.